A new species of Megachile (Eutricharaea) from western Saudi Arabia related to Megachile walkeri (Hymenoptera: Megachilidae) - Engel, Michael S. (Acta entomologica slovenica (Ljubljana), 2008)
A new species of leaf-cutter bee, Megachile (Eutricharaea) ventrisi sp. n., isdescribed and figured from western Saudi Arabia. The species is remarkably similar to M. walkeri Dalla Torre from the same region but differs strikingly in the structure of the metafemoral setae, metasomal scopa, and clypeal integument.
Keywords: čebele; entomologija; nove vrste; Savdska Arabija